THE ILLUSION OF REALITY: STYLISTIC ELEMENTS AND THEMATIC DEPTH IN POE’S A DREAM WITHIN A DREAM - Kalsoom Jahan; Zahir ul Islam Hashmi; Hassan Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study investigates the use of stylistic elements in the poem A Dream Within a Dream by Edgar Allan Poe and their overall contribution towards the themes of lifespan versus understanding of the poetry’s conceptual paradox: reality as opposed to fiction. There are stylish devices employed in "A Dream Within a Dream" that serve to reinforce the central theme of the poem, the dichotomy of truth and untruth in many works of fiction including cinema. To respond to the identified research gaps, the research employs various aspects of literary style in the linguistic evaluation of several prose works including imagery, symbolism, rhyme, and meter among others. For this purpose, field studies focus on how the different components of style work in the text. It is also a conventional historical inquiry and critical perspective with textual analysis of emotional language that is sparsely distributed within the text. The results show Poe’s craft, derivatives, and repetition of symbolisms bring forth blurring effects on the narrators’ real world versus imaginary world walls, creating odds on human existence. Both the grain of sand and the shoreline are symbolic motifs that serve to reiterate the futility of the quest for reality undertaken by the speaker as scabbard, tape, with blue stones, thus enriching the themes of the nervous epigram. It stresses the importance of stylistic criticism in analyzing Poe’s works and provides a new vantage point on the functions of language as a means of self-contemplation on being.